Serum-free medium and hydroxyethyl starch supports cell survival better than Minimal Essential Medium and dextran in organ-cultured mouse corneas. Issue 12 (6th October 2014) - Knels, Lilla; Goetze, Doris; Engelmann, Katrin; Valtink, Monika
Abstract : Background/aims: In a previous study, we observed a deleterious effect of serum-supplemented Minimal Essential Medium (MEM) on human corneal endothelial cell survival in a cell culture model. Consequently, here we studied the effects of conventional, serum-supplemented MEM and a serum-free medium in combination with two different deswelling substances on cell survival in whole corneas in a mouse model. Methods: Murine corneas were cultured for 4 days in MEM+2% fetal calf serum (FCS) or serum-free Human Endothelial-SFM (SFM), both supplemented with either 6% dextran T500 or 7.5% hydroxyethyl starch (HES) 130/0.4. Cells were examined by differential interference contrast microscopy, H&E staining, immunocytochemistry for cleaved caspase-3, Bcl-2, haem oxygenase-1 and immunoblotting for cleaved caspase-3. Results: In MEM, endothelial cells were almost completely lost after 4 days and the number of epithelial cells was markedly reduced. The remaining cells showed fragmented nuclei and were positive for cleaved caspase-3 and strongly positive for Bcl-2. Corneas cultured in SFM retained an almost closed layer of endothelial cells. Fewer cells were positive for Bcl-2, and only a few cells were positive for cleaved caspase-3 even under staurosporine administration. HES supplementation was well tolerated by corneal cells over 4 days, while a 4-day supplementation with dextran resulted in the loss of endothelial and epithelial cells. Conclusions: Serum-free medium, Human Endothelial-SFM, promoted cell survival during corneal organ culture better than MEM+2% FCS. HES 130/0.4 appeared to be tolerated better by the cells than dextran T500.